ئاستی پشتبەستن بە توێژینەوە زانستییەكان لە گەشەپێدانی كاری تەلەڤزیۆندا - حسن, پ. د. هێمن مجيد; حەمەكەریم, سامان حەمەكەریم (Sulaimani Journal for Humanities, 2023)
The subject of this study relates to the discussion of the connection between Kurdistan Regional Televisions and the scientific research of scientific and academic centres. The main issue of the research is the uncertainty and unclearness of the kurdistan region's television channels' reliance on scientific research in order to develop their journalistc proffission and work. The tye of this study is escriptive research relies on survey procedures and survey form to be conducted. The research population consists of journalists who in the Kurdistan Region's TELEVISION channels, the Sample, which consists of 224 media journalists selected as "random" on 10 local and air television channels. In terms of importance, the research is will be important to science media and public expertise in general. The aim of the study was to find out the level of reliance on scientific research by kurdistan's television channel's for development of television work. also knowing the purposes that push the media to rely on the scientific research of the media. The most notable results of the study are: the level of reliance on research with scientific research, for writing and composing journalism genres, and most of them are (to some extent) rely on scientific researchs. The level of reliance on research is moderate, and most of them rely (to some extent) on it, to correct the mistakes and linguistic shortcomings. Majority of journalists who participated in this study do not rely on scientific research for the scientific preparation of television programs and the scientific production and advertisement and the level is low, most of them do not rely on it at all.